E-POSYANDU BERBASIS WEB PADA POSYANDU TERATAI PUTIH DESA BAHALAYUNG MENGGUNAKAN FRAMEWORK CODEIGNITER - Abdullah Ardi; Ayu Safitri (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2021)
Posyandu, which stands for Integrated Health Family Planning Service Post, is a basic health activity organized for people who are assisted by health workers, one of which is the Posyandu Teratai Putih Bahalayung Village. There are several obstacles in this manual system, including Posyandu cadres who often experience difficulties in the data search process, this is because these cadres may not remember the location of the data being searched for or do not understand the data written by other cadres. The system development method used is the Waterfall methodology, from the requirements analysis stage to system testing. For system requirements analysis, the data taken is posyandu data from 2019. For the system design stage, using ERD and DFD, namely Context Diagram and DFD Level 1. For the implementation stage of the system using the Codeigniter framework, programming languages ??PHP, HTML, and Javascript, and the MySQL query language. And the last stage for testing the system uses the Black Box Testing technique.